Understanding medical corruption in China: a mixed-methods study. Issue 4 (17th February 2023) - Fu, Hongqiao; Lai, Yi; Li, Yuanyuan; Zhu, Yishan; Yip, Winnie
Abstract: Medical corruption is a significant obstacle to achieving health-related Sustainable Development Goals. However, the understanding of medical corruption is limited, especially in developing countries. As the largest developing country, China is also plagued by medical corruption. By employing a mixed-methods design and combining data from three resources, this study attempts to examine patterns of medical corruption in China, explore its key drivers and investigate the perceived effectiveness of recent anti-corruption interventions. Using extracted data from 3546 cases on the China Judgments Online website between 2013 and 2019, we found that bribery, embezzlement and insurance fraud accounted for 68.1%, 22.8% and 9.1% of all medical corruption cases, respectively. Bribery was the major form of medical corruption. Approximately 80% of bribe-takers were healthcare providers, and most bribe-givers were suppliers of pharmaceuticals, medical equipment and consumables. Using a nationally representative household survey, we further found that the prevalence of informal payments from patients remained at a low level between 2011 and 2018. In 2018, only 0.4% of outpatients and 1.4% of inpatients reported that they had ever given 'red envelopes' to physicians in the past. Finally, we conducted interviews with 17 key informants to explore drivers of medical corruption and investigated the perceived effectiveness of recent anti-corruption interventions in China. Interview results showed that financial pressure and weak oversight were two main reasons for corrupt behaviours. Interview results also suggested that the anti-corruption campaign since 2012, the national volume-based procurement, and the special campaign against medical insurance fraud had reduced opportunities for medical corruption, implying China's positive progress in combating medical corruption. These findings hold lessons for anti-corruption interventions in China as well as other developing countries.